The Effect Of Eye Exercises Intervention As Myopia Booming Prevention Effort In Children During Online Learning In The Covid-19 Pandemic - Nurul Khotimah; Salva Shofian; Mei Renawati; Riyani Wulandari (P3M Universitas 'Aisyiyah Surakarta, 2022)
Background: During the Covid-19 pandemic, all levels of education must use online learning. Therefore, childrens use gadgets and computers more for a long time, which is made myopia causes in children. The prevalence in Indonesia shows that 10% of 66 million school children (5-19 years old) suffer from refractive errors, namely myopia. While the prevalence of myopia in children Asia is more than 5%, and children in Asia have a higher prevalence in myopia cases of about 29%. Objective: To determine the effect of eye exercises on reducing myopia booming in children during online learning in the COVID-19 pandemic. Methods: This study used a quasi-experimental design with one group pre-test and post-test design. The sample in this study were 15 respondents. The instrument used is the Snellen chart. Results: The results of the paired t statictic test showed that the data before and after the eye exercises intervention showed that in the right eye the p value was 0.035 (Î±<0.05), while for the left eye the p value was 0.031 (Î±<0.05). Conclusion: This study concludes that there is an effect of giving eye exercises intervention on reducing myopia outcomes in children.Â